2015
DOI: 10.1007/s11664-015-3914-2
|View full text |Cite
|
Sign up to set email alerts
|

Humidity Sensor Based on PEDOT:PSS and Zinc Stannate Nano-composite

Abstract: A composite of poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) and zinc stannate (ZnSnO 3 ) has been introduced for impedancebased humidity sensing, owing to its high sensitivity, good stability, very fast response ($0.2 s) and recovery time ($0.2 s), small hysteresis, repeatability, low-cost fabrication and wide range of sensitivity. Both materials were mixed in three different weight percentage ratios, to optimize the performance of the sensors. Best response was observed for 5 wt.% PEDOT:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Among the sensing materials, poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) has been receiving considerable attention for use in sensors because of its outstanding properties, such as high conductivity, good processability, low price, low redox potential, and ability to operate at room temperature 27 29 . Most previous studies that used PEDOT:PSS as an analyte focused on FETs 30 , 31 or electrodes 32 , 33 at the DC level or on a surface acoustic wave (SAW) filter 34 at low frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Among the sensing materials, poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) has been receiving considerable attention for use in sensors because of its outstanding properties, such as high conductivity, good processability, low price, low redox potential, and ability to operate at room temperature 27 29 . Most previous studies that used PEDOT:PSS as an analyte focused on FETs 30 , 31 or electrodes 32 , 33 at the DC level or on a surface acoustic wave (SAW) filter 34 at low frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…In this region, the sensitivity of It was observed that the sensitivity of (Ge 11.5 Se 67.5 Te 12.5 ) 70 Sb 30 was high as compared to (Ge 11.5 Se 67.5 Te 12.5 ) 80 Sb 20 , because by addition of Sb, more molecules of water are adsorbed on the surface of the material, which increases the conductivity of the sample, and hence the sensitivity increases. [33][34][35] CONCLUSION (Ge 11.5 Te 12.5 Se 67.5 ) 80 Sb 20 and (Ge 11.5 Te 12.5 Se 67.5 ) 70 Sb 30 glasses were successfully synthesized through a standard melt-quenching technique and further studied as an impedance-based, frequency-dependent humidity sensor. The XRD graph demonstrates the amorphous nature of the material.…”
Section: Sensing Mechanismmentioning
confidence: 99%
“…So far, PEDOT:PSS has been reported mainly for applications such as i) organic solar cells [5,12], where PEDOT:PSS is used as a hole transport and electron blocking layer, ii) thermoelectric generators [4,13], iii) organic light-emitting diodes (OLEDs) [14,15], touch panels [16,17], paper electronics [18], and organic field-effect transistors (OFETs) [19,20]. Besides these applications, PEDOT:PSS can also be employed as a sensing material to sense humidity [21,22,23,24,25], temperature [24,26], mechanical strain [24], physiological parameters of the human skin [27], drugs [28], cancer biomarkers [29], and gas concentrations [30,31]. However, most of these studies report PEDOT:PSS composites with other functional materials such as carbon nanotubes (CNTs) [26,29], graphene [27,31,32], iron oxide nanoparticles [23], and zinc stannate [22].…”
Section: Introductionmentioning
confidence: 99%